Nutritional risk factors for gestational diabetes mellitus - Singh, Sakshi; Ray, T K; Das, Ranjan; Singh, Abha (Indian Journal of Community Health, 2014)
Background: Gestational diabetes mellitus (GDM) has been observed to be associated with increased perinatal morbidity and mortality. GDM is becoming a public health concern globally as well as in India with fast increasing trend. It affects approximately 14% of all pregnancies. Studies on the association of food items having high glycaemic index with GDM risk are sparse. Most of the literature has focused on typical risk factors like advanced maternal age, family history of diabetes mellitus, history of abortions, previous history of GDM. Objective: To assess the risk of developing GDM in pregnant women consuming food items with high glycemic index. Material and Methods: A hospital based case control study was conducted in Lady Hardinge Medical College and associated hospital with a sample size of 104 (52 cases & 52 controls). For dietary history a validated quantitative food frequency questionnaire was used. The usual pattern of eating during days, weeks and months were asked. The data was compiled and analysed in SPSS version 12. Results: Total 30.8% cases and 13.5% controls gave history of consuming food items having high glycaemic index more frequently (at least once daily). The odds ratio of developing GDM was 2.86(CI -1.06-7.70) among the cases who were taking high glycaemic foods more frequently in comparison to those who were taking occasionally. Conclusions: Risk of developing GDM in high glycemic foods consumers is high. Simple measures like changing dietary patterns, consuming food items with low glycaemic load can contribute significantly in prevention of GDM.